ANALYSIS OF THE COMPATIBILITY OF HIGH SCHOOL PHYSICS MATERIALS WITH LANDSLIDE MATERIALS - Elsa Yanfatriani; Nurul Hazwani; Ahmad Fauzi; - Hamdi; - Syafriani (PILLAR OF PHYSICS EDUCATION, 2021)
Indonesia is prone to landslides. Analysis of the level of suitability of high school physics material with landslide material is important because not all physics material can be integrated with landslide material. Until now, it is not known the level of conformity of high school physics material with landslide material for at least one semester. This study aims to determine the level of suitability of high school physics material with landslide material. This type of research is a descriptive research and uses a qualitative approach. The population used is all material which is a field of physics study and the sample is Physics material for SMA/MA curriculum 2013. The instrument of this research is an analysis sheet of the suitability of Physics material with Landslide material in the form of tables and data collection techniques through documentation studies. The results showed that the physics material for class X semester 1 was in the very appropriate category and semester 2 was in the very appropriate category, the physics material for class XI semester 1 was in the quite appropriate category, the physics material for class XI semester 2 was in the very appropriate category, physics material for class XI semester 2 was in the very appropriate category. class XII semester 1 and semester 2 are in the inappropriate category. This research implies that physics material with a very suitable category to be integrated with landslide material is easy to develop into a physics book integrated with landslide material.